Massjukiella uсrainica is rare for southern Ukraine xanthorioid soredious lichen from urbanized landscapes (CHORNOMORSKI BOTANICAL JOURNAL, 2014)
The ecological peculiarities of the rare for southern Ukraine lichens Massjukiella ucrainica collected from urbanized landscapes are provided.
Keywords: ecology, Massjukiella, Kherson.